Impact Of Port Congestion On Nigeria Economic Growth: An Ardl Approach - Aruwei, P., Melvin U. Eko-Raphael (International Journal of Innovative Finance and Economics Research, 2022)
The study investigates the impact of port congestion on economic growth in Nigeria using the Autoregressive Distributed Lag (ARDL) approach to cointegration and error correction modelling to analyze time series data from 1995 to 2019. The study finds the existence of a long run relationship among the variables and that Cargo Throughput (CTP), Ship Turnaround Time (STT) and Port Infrastructural Development (PID) which are the independent variables employed in the study showed positive but insignificant relationship with the dependent variable RGDP indicating that benefits imbedded in the ports in Nigeria is not harnessed, primarily due to the over dependence on crude oil export as the main source of foreign exchange earnings. The short run dynamic ECM is negative and statistically significant indicating that port congestion in Nigeria is a short run problem, though it can be corrected in the long run if the government can make deliberate effort in putting the necessary infrastructures in place. The study therefore recommends that government should make conscious effort to invest more in the ports through needed infrastructures in order to harness the gains from an efficient port. The ARDL model used in the study is also stable based on the CUSUM and CUSUMQ Test. Congestion, Ports, Economic Growth, Autoregressive Distributed Lag (ARDL)
The study investigates the impact of port congestion on economic growth in Nigeria using the Autoregressive Distributed Lag (ARDL) approach to cointegration and error correction modelling to analyze time series data from 1995 to 2019.
Keywords: Congestion; Ports; Economic Growth; Autoregressive Distributed Lag (ARDL)